2018
DOI: 10.22159/ajpcr.2018.v11i9.26847
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy of Sequential Use of Gonadotropin-Releasing Hormone Analog - Levonorgestrel-Releasing Intrauterine System in Medically Ill Women With Symptomatic and Relatively Large Adenomyosis

Abstract: Objectives:To evaluate the clinical outcome of sequential therapy of gonadotropin-releasing hormone (GnRH) analog, followed by the levonorgestrelreleasing intrauterine system in medically ill women with relatively large and symptomatic adenomyosis. Methods:A prospective cohorts study conducted in the Obstetrics and Gynaecology Department, Al-Yarmouk teaching hospital in Baghdad/Iraq from June 2016 to January 2018. 32 women, 40 years and above who complete their family and had significant medical disease along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We included 38 trials, reporting on data from 5175 women ( Table I ) ( Fedele et al , 1997 ; Maia et al , 2003 ; Hadisaputra and Anggraeni, 2006 ; Bragheto et al , 2007 ; Kim et al , 2007 ; Cho et al , 2008 ; Kang et al , 2009 ; Sheng et al , 2009 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhou et al , 2011 ; Kelekci et al , 2012 ; Ekin et al , 2013 ; Liu et al , 2014 ; Zhang et al , 2014 ; Huang et al , 2015 ; Lee et al , 2015 , 2019 ; Long et al , 2015 ; Chong et al , 2016 ; Liu et al , 2016 ; Park et al , 2016 ; Hai et al , 2017 ; Huang et al , 2017 ; Liu et al , 2017 ; Osuga et al , 2017 ; Yang et al , 2017 , 2019 ; Alizzi, 2018 ; Guo et al , 2018 ; Jun-Min et al , 2018 ; Li et al , 2018 , 2020 ; Huang et al , 2020 ; Lin et al , 2020 ; Sun et al , 2020 ; Kwack et al , 2021 ; Sun et al , 2021 ). There were six (16%) randomized controlled trials (RCTs) ( Hadisaputra and Anggraeni, 2006 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhang ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 38 trials, reporting on data from 5175 women ( Table I ) ( Fedele et al , 1997 ; Maia et al , 2003 ; Hadisaputra and Anggraeni, 2006 ; Bragheto et al , 2007 ; Kim et al , 2007 ; Cho et al , 2008 ; Kang et al , 2009 ; Sheng et al , 2009 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhou et al , 2011 ; Kelekci et al , 2012 ; Ekin et al , 2013 ; Liu et al , 2014 ; Zhang et al , 2014 ; Huang et al , 2015 ; Lee et al , 2015 , 2019 ; Long et al , 2015 ; Chong et al , 2016 ; Liu et al , 2016 ; Park et al , 2016 ; Hai et al , 2017 ; Huang et al , 2017 ; Liu et al , 2017 ; Osuga et al , 2017 ; Yang et al , 2017 , 2019 ; Alizzi, 2018 ; Guo et al , 2018 ; Jun-Min et al , 2018 ; Li et al , 2018 , 2020 ; Huang et al , 2020 ; Lin et al , 2020 ; Sun et al , 2020 ; Kwack et al , 2021 ; Sun et al , 2021 ). There were six (16%) randomized controlled trials (RCTs) ( Hadisaputra and Anggraeni, 2006 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhang ...…”
Section: Resultsmentioning
confidence: 99%
“…Only seven (18%) studies had a clearly defined primary outcome ( Fedele et al , 1997 ; Maia et al , 2003 ; Sheng et al , 2009 ; Chong et al , 2016 ; Liu et al , 2017 ; Osuga et al , 2017 ; Sun et al , 2021 ) and 11 (29%) studies stated multiple or all reported outcomes to be the primary ( Hadisaputra and Anggraeni, 2006 ; Bragheto et al , 2007 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhou et al , 2011 ; Kelekci et al , 2012 ; Ekin et al , 2013 ; Liu et al , 2014 ; Long et al , 2015 ; Li et al , 2018 ; Huang et al , 2020 ). Twenty studies (53%) did not define a primary outcome at all ( Kim et al , 2007 ; Cho et al , 2008 ; Kang et al , 2009 , 2010 ; Zhang et al , 2014 ; Huang et al , 2015 ; Lee et al , 2015 , 2019 ; Liu et al , 2016 ; Park et al , 2016 ; Hai et al , 2017 ; Huang et al , 2017 ; Yang et al , 2017 , 2019 ; Alizzi, 2018 ; Guo et al , 2018 ; Jun-Min et al , 2018 ; Li et al , 2018 ; Lin et al , 2020 ; Sun et al , 2020 ; Kwack et al , 2021 ). Most of these studies described the aims in non-specific terms, such as ‘clinical efficiency’, but without defining the terms ‘clinical’ or ‘efficiency’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation